Sistem Manajemen Inventory dan Costing Produk pada Minimarket Puri Mart Berbasis Web - Dwiputri, Ririt; Jarti, Nanda; Angiani, Windi Eka (LPPM Universitas Ibnu Sina, 2024)
In inventory management, computerized data collection is needed, therefore the warehouse and store section can handle the data collection process easily and minimize errors and shorten the time required. control any costs that may be too large or too small in the production process. This research was conducted at the Puri Mart Minimarket. The process of checking the stock of goods at the Puri Mart minimarket still uses the manual method, namely seeing the stock directly one by one in the warehouse, the manual work system by recording in excel one by one which requires the Puri Mart minimarket to update its working system so it doesn't take too much time to check goods one by one and if there is a dispute over the number of goods. The purpose of this study is to produce an inventory and costing management system at the Puri mart minimarket and make it easier for the Puri mart minimarket admin to determine the selling price of a product, so that it can provide benefits for the minimarket. The result of this research is a web-based management system that is able to record, manage and print stock and price reports at the Puri Mart Minimarket which consists of calculating the number of incoming and outgoing stock and the price of a product. Data collection methods used in this study were interviews, observation, and literature study. The system development method used is Waterfall with UML (Unified Modeling Language) modeling which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams. The system is designed web-based using the PHP programming language, using MySQL as a database and using Black box testing